2022
DOI: 10.3390/vaccines10020186
|View full text |Cite
|
Sign up to set email alerts
|

Which Type of the Promising COVID-19 Vaccines Produces Minimal Adverse Effects? A Retrospective Cross-Sectional Study

Abstract: Since the declaration of Coronavirus-2019 (COVID-19) as a pandemic by the World Health Organization (WHO), it was clear that vaccination is the best way to overcome it. Sinopharm, AstraZeneca and Pfizer were the first vaccines introduced to defeat it. To recognize the short-term adverse effects among Iraqi health care workers (HCWs) after vaccination, the three COVID-19 vaccines that are currently available in Iraq were compared. An online survey was distributed to Iraqi HCWs who had received at least one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
4
11
2
Order By: Relevance
“…The local and systemic side effects were significantly more frequent among the adenoviral vector vaccines group (61.3, and 68.3%) than the inactivated virus vaccinated group (41.8, and 45.1%). This finding is consistent with the results of multiple previous studies that reported that the Chinese inactivated vaccines, i.e., BBIBP-CorV and CoronaVac induced fewer side effects than either adenoviral vector-based mRNA-based vaccines ( 18 , 19 , 40 42 ). Moreover, the reported side effects were generally mild in patients who received inactivated vaccines ( 19 , 22 , 41 44 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The local and systemic side effects were significantly more frequent among the adenoviral vector vaccines group (61.3, and 68.3%) than the inactivated virus vaccinated group (41.8, and 45.1%). This finding is consistent with the results of multiple previous studies that reported that the Chinese inactivated vaccines, i.e., BBIBP-CorV and CoronaVac induced fewer side effects than either adenoviral vector-based mRNA-based vaccines ( 18 , 19 , 40 42 ). Moreover, the reported side effects were generally mild in patients who received inactivated vaccines ( 19 , 22 , 41 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, 38.1% of our participants took post-vaccination medications, mainly Paracetamol, to manage these side effects and 1.1% reported being hospitalized, thus, confirming the mildness of these side effects. In Iraq, 57.2% of the vaccinated healthcare workers took Paracetamol, especially among those vaccinated with BNT162b2 and AZD1222, and 8.7% of them sought medical care ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 Many studies were done to determine side effects according to the type of vaccine following vaccination with COVID-19 vaccines in Arabian countries like Iraq, Saudi Arabia and Jordan. [10][11][12] Despite a large number of studies regarding the efficacy and safety of COVID-19 vaccines, only two randomized clinical trials (RCTs) and limited observational studies outlined the gender disparity toward COVID-19 vaccine adverse effects.…”
mentioning
confidence: 99%
“…Multiple studies among different populations were conducted to assess the side effects following the COVID-19 vaccine: many of them found that the inactivated COVID-19 vaccine induced fewer side effects than other types of COVID-19 vaccines did [ 26 , 27 , 28 , 29 , 30 , 31 ]. In this study, about half of the participants did not experience any side effects after the first dose of the inactivated COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%